Association Between Variation in Red Cell Size and Multiple Aging-Related Outcomes. (7th September 2020) - Kim, Kyoung Min; Lui, Li-Yung; Browner, Warren S; Cauley, Jane A; Ensrud, Kristine E; Kado, Deborah M; Orwoll, Eric S; Schousboe, John T; Cummings, Steven R
Abstract: Background: We tested whether greater variation in red blood cell size, measured by red cell distribution width (RDW), may predict aging-related degenerative conditions and therefore, serve as a marker of biological aging. Methods: Three thousand six hundred and thirty-five community-dwelling older men were enrolled in the prospective Osteoporotic Fractures in Men Study. RDW was categorized into 4 groups (≤13.0%, 13.1%–14.0%, 14.1%–15.0%, and ≥15.1%). Functional limitations, frailty, strength, physical performance, and cognitive function were measured at baseline and 7.4 years later. Falls were recorded in the year after baseline; hospitalizations were obtained for 2 years after baseline. Mortality was assessed during a mean of 8.3 years of follow-up. Results: Participants with greater variability in red cell size were weaker, walked more slowly, and had a worse cognitive function. They were more likely to have functional limitations (35.2% in the highest RDW category vs 16.0% in the lowest, p < .001) and frailty (30.3% vs 11.3%, p < .001). Those with greater variability in red cell size were more likely to develop new functional limitations and to become frail. The risk of having 2 or more falls was also greater (highest 19.2% vs lowest 10.3%, p < .001). The risk of hospitalization was higher in those with the highest variability (odds ratio [95% confidence interval], 1.8 [1.3–2.5]) compared with the lowest. Variability in red cell size was related to total and cause-specific mortality. Conclusion: Greater variability in red cell size is associated with diverse aging-related outcomes, suggesting that it may have potential value as a marker for biological aging.